Target depth estimation by frequency interference matching for a deep vertical array. (15th January 2022) - Zhou, Lisheng; Zheng, Guangying; Yang, T.C.
Abstract: A vertical line array can be deployed in deep water below the critical depth, i.e., the depth where the sound speed equals the sound speed at the surface, to take advantage of the lower ambient noise level, relative to above the critical depth for target detection. The depth of a source can be estimated exploring the interference between the direct and reflected signals described by Lloyd's mirror theory. Existing methods for source-depth estimation assume either a source transmitting a pulsed signal or a source traveling a straight line at a constant depth. For the latter, the source depth can be estimated after collecting observations over a sufficiently large domain of ranges. A method is proposed here that can estimate the source depth using a short snapshot of the random broad band signal, and can thus estimate the source depth semi-instantaneously, even as the source changes course and/or depth. An incoherent matched beam processing method is used matching the peak beam power measured from data as a function of frequency with a replica peak beam power spectrum for a hypothesized source depth. The performance of the proposed method is evaluated using simulated data and validated with experimental data from the South China Sea.